2022
DOI: 10.1109/access.2022.3145710
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable Business Framework Using Solar and Bio-Energy to Instate Incessant Power in Rural India: Optimal Scheduling, Smart Metering, and Economic Viability

Abstract: In this paper, a profitable strategy of utilizing solar and bio-energy available in a rural location for meeting the energy deficit is discussed. The proposed model can provide 24-hour continual power supply to the vicinity without the need of any battery. The land requirement is minimal in the proposed model making it cost-effective for implementation. The paper provides a step by step procedure to optimally size the solar and bio-power plants and schedule their operation for maximum utility. A programmable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The technical and financial analysis carried out for two villages and 768 households showed that the system provides 24/7 power and is also cost-effective due to the relatively short payback period (less than 8 years). In addition, the implementation of the strategy provided benefits such as the reduction of greenhouse gas emissions (by 93%), the automatic control of electricity theft, biofertilizers and the improvement of the natural environment [43]. For Indonesia in the Merauke area, Regency assessed the use of renewable energy potential from biomass, solar and wind power to reduce dependence on fossil energy and offset the increase in electricity consumption at a time of economic and population growth.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The technical and financial analysis carried out for two villages and 768 households showed that the system provides 24/7 power and is also cost-effective due to the relatively short payback period (less than 8 years). In addition, the implementation of the strategy provided benefits such as the reduction of greenhouse gas emissions (by 93%), the automatic control of electricity theft, biofertilizers and the improvement of the natural environment [43]. For Indonesia in the Merauke area, Regency assessed the use of renewable energy potential from biomass, solar and wind power to reduce dependence on fossil energy and offset the increase in electricity consumption at a time of economic and population growth.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Solar energy studies have been conducted using software such as PVsyst, PV-Online, System Avisor Model-SAM, Solar-GIS, and RETScreen [21][22][23]. In addition, there are PVGIS and PVWatts software programs that have not been researched much in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The daily generating energy of a photovoltaic power station affects the power consumption of the local area [1][2][3], while the photovoltaic power generation has a relationship with environmental factors, such as sunshine duration, temperature, etc. Thus, the prediction of the generating energy helps the local power grid system to improve foreseeability and to create a proper generating schedule [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%